New scheduling rule improves pipeline efficiency - Cafaro, Vanina (2011)
A new rule prioritizing product delivery to the eligible terminal closest to the one being currently served reduces total accumulated idle volume by about 40% and decreases the number of cut operations. Different priority arrays lead to different delivery schedules, strongly affecting cost-efficiency of the solution achieved. Prioritizing nearest-to-refinery terminals, for instance, may reduce the total volume of segments stopped, but the number of stripping operations will surely increase. Prioritizing the farthest terminals, however, may increase the number and volume of pipeline stoppages. Part 1 of this series (OGJ, Aug. 1, 2011, p. 98) discussed development of the discrete event simulation system on “Arena.” This concluding second part applies the system tomanagement of a real-world products pipeline with a single input and multiple delivery points. The approach described allows use of emerging simulation- based optimization tools to improve performance of the resulting schedules. Future work will focus on developing efficient priority rules combined with heuristic search and rigorous formulations to find cost-efficient and robust solutions for detailed scheduling of multiproduct pipeline networks with different configurations.